Performance evaluation of ECMWF monthly rainfall forecasts in the Limpopo River Basin - Vigneswaran, Kayathri; Ghosh, Surajit; Retief, H.; Garcia Andarcia, Mariangel; Dickens, Chris (International Water Management Institute, 2024)
This study evaluates the performance of the European Centre for Medium-Range Weather Forecasts (ECMWF) seasonal rainfall forecasts provided by Limpopo River Basin's (LRB) Digital Twin using Climate Hazards Group InfraRed Precipitation with Station (CHIRPS) dataset as a reference for the period of 2017 to 2024. The primary aim is to assess forecast skill across different climate zones within the LRB, characterized by varying climatic conditions from semi-arid to temperate.